Análisis de rentabilidad ecónomica y financiera en la cafetería El Tamal Lojano de la ciudad de Loja. - Angamarca Carrión, Lizette Del Cisne (2010)
The financial and economic analysis done to the financial statements of the Tamal Lojano Cafeteria in 2008 and 2009, allowed us to evaluate the position of the company in various aspects through the application of ÍNDICEs to measure the economic and financial profitability and finally communicating the results obtained the highest authority in the CAFETERÍA so that you know and can take corrective actions. Once analyzed the Income Statement and Statement of Financial Position of Tamal Lojano Cafeteria and by applying the indices were able to assess the position of the company in different aspects and the value that corresponds mainly on account of economic and financial viability in the periods under review. The methodology started from obtaining the financial statements and using them was held vertical and horizontal analysis, and by the application of financial indicators and indices were determined economic and financial profitability of the company .of 74.83 at 228.88 on profitability and financial profitability.